Identification of prevalence and degree of infection of paramphistomatosis of cattle according to the age: Case of districts of the Republic of Karakalpakstan - Bazarbayeva Aynura; Kalenderov Azat (BIO Web of Conferences)
According to our research, the ecological situation in Karakalpakstan has gotten worse recently. This includes the Aral Sea tragedy, the drying up of many lakes due to droughts, the loss of most of the natural gastrotilax foci, as well as other paramphistomata like P.ichikawae and rare cases of L.scotiae. The purpose of this study was to assess the prevalence of paramphistomatosis in cattle across different districts of the Republic of Karakalpakstan and to evaluate the infection's impact based on the animals' age. Research was conducted in the districts of Tortkul, Amudarya, Ellikkala, and Beruni. Methods included helmintoovoscopic examination of dung samples from 478 cattle and comprehensive helminthological dissection of 40 cattle. Results indicated an average infection rate of 3.9%, with the highest prevalence in Amudarya district (5.5%) and the lowest in Tortkul district (3.3%). Age-wise, infection rates were 3.5% in calves (6-12 months), 3.7% in young cattle (1-2 years), and 2.5% in older cattle (2 years and older). The study concluded that paramphistomatosis is a significant issue in Karakalpakstan, with notable age and regional variations. The Amudarya district, with more natural freshwater mollusc biotopes, exhibited a higher prevalence, suggesting a correlation between mollusc populations and infection rates.